Investigating Factors Affecting Location by Meta-Analysis - vahide nori; Afson Mahdavi; Fatemeh Mohammad Niae Qaraee (تحقیقات کاربردی علوم جغرافیایی)
The attachment to the place is the emotional relationship of the individual to the place, which is rooted in the person's past qualities and experiences that the place should be able to meet the needs and expectations of the individual, and also the place must meet the capacity to meet those needs and expectations. The attachment to the location is based on the cognitive, emotional, and functional interaction between individuals, groups, and physical-social location over time. The purpose of this study was to use the meta-analysis method to analyze the results of research on attachment to the place. In order to perform a meta-analysis, 75 researches were conducted in this regard. Among the 18 studies conducted during the years 2006-2019, in the field of attachment to the place were selected. In the first step, the evaluation of selected research, homogeneous assumptions and publication error was studied; accordingly, the findings indicated the heterogeneity of the size of the effect and the non-dominance of the published studies. In the second step, the coefficient of effect size was evaluated using the second version of CMA software. The results showed that the size of the effect or coefficient of influence of the identified factors is 0/376, which is evaluated according to the Cohen's interpretation system. Overall, the results indicate that the identified factors have a moderate effect on attachment to the location.